(untitled) (Anwer Khan Modern Medical College Journal, 2020)
Emphysematous pyelonephritis(EPN) is an acute necrotic infection of the kidney which is characterized by presence gas in the renal parenchyma. Uncontrolled diabetes mellitus and obstruction of the urinary tract are the main predisposing factors and Mycobacterium tuberculosis is a rare causative pathogen. One of the major health problem faced particularly by the developing world since ages is that of tuberculosis (TB). Genitourinary tuberculosis (GUTB) is the second most common extra-pulmonary TB, with kidney being the most frequent site of infection. We herein report a case of a patient with uncontrolled diabetes mellitus who was admitted through emergency department with symptoms of pyelonephritis. Imaging revealed the gas in the renal parenchyma establishing the diagnosis and as we found sterile pyurea we searched for Mycobacterium tuberculosis. GUTB was diagnosed and was treated successfully with anti TB drugs. EPN is a medical emergency and once diagnosed, attention must be paid to avoid high mortality rates. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 73-77